Statistical Interpretation of Semi‐Continuous Anaerobic Digestion Experiments on the Laboratory Scale. Issue 4 (3rd February 2016) - Hofmann, Josephine; Peltri, Gregor; Sträuber, Heike; Müller, Liane; Schumacher, Britt; Müller, Ulf; Liebetrau, Jan
Abstract: The importance of thorough experimental design, implementation, and interpretation of laboratory experiments is known but rarely considered in continuous anaerobic digestion experiments. Especially in the evaluation of small effects on gas yields, e.g., by substrate disintegration, the usual methods such as the use of single digesters or the mere comparison of mean values often reach their limits. A proper statistical interpretation will be demonstrated on four examples of semi‐continuous laboratory‐scale anaerobic digestion experiments that investigated the effects of substrate disintegration on biogas yields. Power analysis was performed for one exemplary experimental setup. In this particular case, the power analysis showed that, with digester duplicates per treatment, a minimum 6 % difference in biogas yield could be significantly detected. Abstract : When evaluating small effects on biogas production, the usual methods such as single digesters or the mere comparison of mean values often reach their limits. Since small effects appear after substrate disintegration, proper statistical interpretation of the biogas production and appropriate experimental design focusing on replication are demonstrated by four exemplary disintegration experiments.